Low‐Cost Sensor‐Rich Fluidic Elastomer Actuators Embedded with Paper Electronics. (19th August 2020) - Yang, Tilo H.; Shintake, Jun; Kanno, Ryo; Kao, C. Robert; Mizuno, Jun
Abstract : Fluidic Elastomer Actuators In article number 2000025, Tilo H. Yang, Jun Mizuno, and co‐workers develop a low‐cost, intelligent fluidic elastomer actuator (FEA) by incorporating paper electronics (PEs). The PE‐embedded FEAs can acquire rich information: deformation of the actuators, shape of external objects, proximity, and types of material in contact. This work provides a low‐cost and mass‐reproducible integration strategy paving the way for highly sensorized intelligent soft robotic systems.